Moral Injury and Tragic Sensibility: Reframing the Iraqi Refugee Crisis - Dunn, Shannon (Journal of religious ethics, 2021)
Since Jonathan Shay's work with Vietnam veterans, moral injury has largely focused on the harm done to soldiers' moral character through their participation in warfare. This essay argues for the inclusion of noncombatants in the scope of inquiry involving moral injury. Specifically, it argues for the necessity of ordinary citizens assuming responsibility for the moral injury done to soldiers and civilians alike in the post-9/11 wars.